Quad-rotor adaptive sliding mode control using only position and yaw sensors: Generalized relative degree approach. Issue 1 (January 2022) - Alfayizi, Mohammed; Shtessel, Y.; Edwards, C.
Abstract: An output tracking controller design is proposed for perturbed Quad-Rotor Unmanned Aerial Vehicles (QR-UAV) using a generalized relative degree approach that allows employing only four measurements of the QR-UAV states, position ( x, y, z ) and yaw angle ( ψ ), instead of the traditional six variables. Adaptive Super-Twisting (ASTW) control is applied for controlling the yaw angle ( ψ ) in the presence of perturbations with bounded derivatives and unknown bounds. The relative degree approach allows the application of Adaptive Continuous High Order Sliding Mode (ACHOSM) control for controlling the position states ( x, y, z ), in a single loop, in the presence of smooth perturbations with bounded derivatives and unknown bounds. The proposed single loop ASTW and the ACHOSM controllers, with non-overestimated control gains, drive the position trajectory and yaw tracking errors to zero asymptotically in the absence of dynamics of actuators and sensors. Finite convergent time Filtering HOSM differentiators are used to facilitate the ACHOSM controllers in the presence of the noisy measurements. The proposed single loop sliding mode controllers have been validated via simulations.